(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In this article the authors examine the intonation of interrogative, exclamatory sentences in a quasispontaneous and spontaneous speech of the Kazakh language. The authors highlight the theoretical data on the research of the Kazakh intonation, as well as the results of an experimental study of intonation in the Kazakh spontaneous speech.